How can the overtreatment rate of "see and treat" approach be reduced in women with high-grade squamous intraepithelial lesion on cervical cytology? - Chumnan Kietpeerakool (2018)
The aim of this study was to determine the incidence and predictors of overtreatment in "see and treat" approach using loop electrosurgical excision procedure (LEEP) in women with high-grade squamous intraepithelial lesion (HSIL) on cervical cytology. The overtreatment was considered when LEEP specimens contained no cervical pathology. Between January 2001 and April 2006, 446 women with HSIL on Pap smear underwent colposcopy followed by LEEP at Chiang Mai University Hospital. Mean age of these patients was 45.6 years with a range of 25-78 years. One hundred and twenty-one (27.1%) women were menopausal. Unsatisfactory colposcopy was observed in 357 (80.0%) women. Of 446 women, histologically-confirmed HSIL, invasive cancer, low-grade squamous intraepithelial lesions, and adenocarcinoma in situ were detected in 330 (74.0%), 76 (17.0%), 9 (2.0%), and 5 (1.1%), respectively. The overtreatment rate on LEEP specimens was noted in 26 women or 5.8% (95% confidence interval [CI] = 3.8 to 8.4) of 446 women. By multivariate analysis, postmenopausal status was the only significant independent predictor of overtreatment with an adjusted odds ratio of 2.89 (95% CI = 1.30 to 6.43, P = 0.009). When postmenopausal women were excluded from analysis, the overtreatment rate was reduced to only 4.0%. In conclusion, "see and treat" approach appears to be an appropriate strategy in managing women with HSIL cytology. The overtreatment rate could be reduced when such policy is limited for premenopausal women.